Tunable surface modification of silica nanoparticles through `click' chemistry - Chandran, S. Prathap; Hotha, Srinivas; Bhagavatula L. V. Prasad (Current Science, 2008)
Tuning the surface functionality of silica nanoparticles through a `click' chemistry-based protocol is demonstrated. Pyrene, a fluorophore that displays excimer emission specifically at higher density/concentration is chosen for highlighting the fidelity of surface functionalization. The UV-visible absorbance of the pyrene chromophore capping the nanoparticle is used to determine the amount of pyrene units present on the surface of a silica nanoparticle.
Keywords: pyrene; silica nanoparticles; surface functionality; `Click' chemistry

Time and temperature effects on the digestive ripening of gold nanoparticles: is there a crossover from digestive ripening to ostwald ripening? - Sahu, Puspanjali; Bhagavatula L. V. Prasad (Langmuir, 2014)
The effects of time and temperature on the gold nanoparticle sizes obtained by digestive ripening have been investigated. In digestive ripening, a polydisperse colloid, upon refluxing with a surface-active ligand in a solvent, gets converted to a nearly monodisperse one. In this study, a polydisperse gold nanoparticle system was heated in 4-tert-butyltoluene with hexadecanethiol at different temperatures, viz., 60, 90, 120, 150, and 180 degrees C for different time periods, and the trends in particle size variations were recorded. At lower temperatures such as 60 and 90 degrees C, after the initial narrowing of the size distribution, the particle sizes remain constant even though the refluxing step is continued for 24 h, substantiating the prevalence of the digestive ripening process. However, at elevated temperatures (120, 150, and 180 degrees C) particle sizes grow continuously, indicating a deviation from the digestive ripening behavior to an Ostwald ripening-type phenomenon.